Do forest reserves help maintain pollinator diversity and pollination services in tropical agricultural highlands? A case study using Brassica rapa as a model - Escobedo-Kenefic, Natalia; Cardona, Edson; Arizmendi, María del Coro; Domínguez, César A. (Frontiers in Bee Science, 2024)
Habitat loss and fragmentation have negative impacts on pollinator populations and thus on the pollination services they provide. Negative effects can be lessened by the presence of forest remnants that serve as refuges and sources of food for pollinators. However, few studies have analyzed the influence of highly heterogeneous agricultural landscapes (as commonly found in many developing countries), on pollination services. We compared native bee diversity, pollination visitation, and fruit set of Brassica rapa L. between two land use conditions (sites maintaining more than 15% of the original forest coverture [Moderately Modified], and sites with less of 10% [Highly Modified]) in the highlands of Guatemala. Native bee diversity was higher in HM areas, although social bees were more abundant in MM sites. We did not find differences in pollinator visitation rate between conditions. HM sites were mainly visited by honeybees (Apis mellifera Linnaeus), while native bees and syrphid flies were more frequent in the MM condition. Fruit set was significantly higher in MM sites and was positively affected by natural forest areas. Experiments on pollen limitation and on pollinator efficiency stressed the importance of native pollinators in fruit production, especially in moderately modified areas. Our results highlight the role of forest remnants on the provision of pollination services in tropical agricultural highlands and underline the relevance of appropriate management of introduced bees such as A. mellifera.